Assessment of metal and bacterial contamination in cultivated fish and impact on human health for residents living in the Mekong Delta. (November 2016) - Chanpiwat, Penradee; Sthiannopkao, Suthipong; Widmer, Kenneth; Himeno, Seiichiro; Miyataka, Hideki; Vu, Ngoc-Ut; Tran, Van-Viet; Pham, Thi-Tuyet-Ngan
Abstract: Fish is the main source of animal protein and micronutrients for inhabitants in the lower Mekong River basin. Consumption of fish in the basin ranges from 41 to 51 kg capita −1 year −1 . Thus, concerns of human health impacts caused by daily intake of metals contained in fish, and the incidence of bacterial contamination from Listeria and Escherichia coli have been raised. This study was conducted to 1) determine concentrations of metals, fecal indicator organisms, and Listeria spp. in cultivated common diet fish, and 2) assess human health risks as results of fish consumption on a daily basis. The results showed significant impacts of metal accumulation in fish especially from the intensive aquaculture. Chemical use to promote the rapid allometric growth of fish was expected to be the explanation for this finding. Concentrations of metals contained in different fish species were not statistically different with the exceptions of Na, Mn, and Zn. This might be due to the mobility of elements in aquaculture farms. Listeria and E. coli log CFU/g were 1.36 ± 0.11 (standard error) and 1.57 ± 0.1 s.e., respectively with higher counts observed in samples collected in market sites. Lastly, for human health risk assessment via fish consumption, it was found that hazard quotients of consuming As, Cu, and Zn contained in all fish species could contribute adverse health effects to the local residents (hazard quotients higher than 1). Therefore, risk management measures must be promoted and implemented in all study areas to reduce potential risks to local Vietnamese residents. Highlights: There were metals and microbial contaminations in fish in the southern Vietnam. Different methods of aquaculture cultivations affect metal concentrations in fish. Health impacts of Zn, As, and Cu are expected from daily fish consumption. Low infection risks of Listeria spp. and Escherichia coli in cooked fish (<2 log/g). Processing methods may cause higher microbial contamination in market fish.